Hyperpolarization-activated cyclic nucleotide gated channels: a potential molecular link between epileptic seizures and Aβ generation in Alzheimer’s disease - Saito, Yuhki; Inoue, Tsuyoshi; Zhu, Gang; Kimura, Naoki; Okada, Motohiro; Nishimura, Masaki; Kimura, Nobuyuki; Murayama, Shigeo; Kaneko, Sunao; Shigemoto, Ryuichi; Imoto, Keiji; Suzuki, Toshiharu (Molecular neurodegeneration, 2012)
One of the best-characterized causative factors of Alzheimer's disease (AD) is the generation of amyloid-β peptide (Aβ). AD subjects are at high risk of epileptic seizures accompanied by aberrant neuronal excitability, which in itself enhances Aβ generation. However, the molecular linkage between epileptic seizures and Aβ generation in AD remains unclear. X11 and X11-like (X11L) gene knockout mice suffered from epileptic seizures, along with a malfunction of hyperpolarization-activated cyclic nucleotide gated (HCN) channels. Genetic ablation of HCN1 in mice and HCN1 channel blockage in cultured Neuro2a (N2a) cells enhanced Aβ generation. Interestingly, HCN1 levels dramatically decreased in the temporal lobe of cynomolgus monkeys (Macaca fascicularis) during aging and were significantly diminished in the temporal lobe of sporadic AD patients. Because HCN1 associates with amyloid-β precursor protein (APP) and X11/X11L in the brain, genetic deficiency of X11/X11L may induce aberrant HCN1 distribution along with epilepsy. Moreover, the reduction in HCN1 levels in aged primates may contribute to augmented Aβ generation. Taken together, HCN1 is proposed to play an important role in the molecular linkage between epileptic seizures and Aβ generation, and in the aggravation of sporadic AD.